Early defenders of women’s intellectual rights: Wollstonecraft’s and Rokeya’s strategies to promote female education - Hasan, Md. Mahmudul (Routledge, 2018)
Given that social constructions and deeply embedded cultural misapprehensions about gender, together with conventional views of female intellectual ability, denied women entry into institutional education, Wollstonecraft and Rokeya mounted a literary campaign to promote female education in their respective societies. They argued that female education would not only advance the cause of women, it would also be conducive to the interests ofmen as well as the wider society. Given these cultural backgrounds, this article examines the traditional notion of gendered intellect within their respective cultural contexts, discusses their arguments against cultural mythologies of women’s cerebral capabilities, and makes an in-depth analysis of their strategies for, and philosophy of, female education. It analyses social restrictions on women’s education and pits them against Rokeya’s and Wollstonecraft’s ideas that envisage equal educational opportunities for both genders.